Spheroid Culture of Mesenchymal Stromal Cells Results in Morphorheological Properties Appropriate for Improved Microcirculation. Issue 8 (19th February 2019) - Tietze, Stefanie; Kräter, Martin; Jacobi, Angela; Taubenberger, Anna; Herbig, Maik; Wehner, Rebekka; Schmitz, Marc; Otto, Oliver; List, Catrin; Kaya, Berna; Wobus, Manja; Bornhäuser, Martin; et al.
Abstract: Human bone marrow mesenchymal stromal cells (MSCs) are used in clinical trials for the treatment of systemic inflammatory diseases due to their regenerative and immunomodulatory properties. However, intravenous administration of MSCs is hampered by cell trapping within the pulmonary capillary networks. Here, it is hypothesized that traditional 2D plastic‐adherent cell expansion fails to result in appropriate morphorheological properties required for successful cell circulation. To address this issue, a method to culture MSCs in nonadherent 3D spheroids (mesenspheres) is adapted. The biological properties of mesensphere‐cultured MSCs remain identical to conventional 2D cultures. However, morphorheological analyses reveal a smaller size and lower stiffness of mesensphere‐derived MSCs compared to plastic‐adherent MSCs, measured using real‐time deformability cytometry and atomic force microscopy. These properties result in an increased ability to pass through microconstrictions in an ex vivo microcirculation assay. This ability is confirmed in vivo by comparison of cell accumulation in various organ capillary networks after intravenous injection of both types of MSCs in mouse. The findings generally identify cellular morphorheological properties as attractive targets for improving microcirculation and specifically suggest mesensphere culture as a promising approach for optimized MSC‐based therapies. Abstract : Stem cell‐based approaches are the future in clinical therapy. However, current cell expansion protocols affect cell mechanics and morphology resulting in inefficient cell circulation, a critical process for targeted delivery. The comparison between 2D (plastic adherent) and 3D (mesensphere) cultured mesenchymal stromal cells identifies 3D cultures to promote mechanical and morphological properties appropriate for circulation.